A guide to implementing and evaluating a vocational rehabilitation counselling program for individuals injured in motor vehicle accidents in Newfoundland and Labrador - Edwards, Ethel Ann, 1967- (1997)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1997. Education Bibliography: leaves 98-102